Netralitas Aparatur Sipil Negara dalam Pemilu di Samarinda: Analisis Hukum dan Pengawasan - Andi Mardatila; Syaharie Ja’ang (Wadah Inovasi Indonesia, 2024)
This study examines the legal analysis of the neutrality of State Civil Apparatus (ASN) in Samarinda during the implementation of the General Election. The research focuses on the legal framework governing ASN neutrality, the challenges faced by oversight bodies in enforcing these regulations, and the implications for democratic processes. The findings reveal that while legal provisions such as Law No. 20 of 2023 on ASN and Law No. 7 of 2017 on General Elections provide a strong foundation for neutrality, practical challenges including bureaucratic delays, limited authority of oversight bodies, and political interference hinder effective enforcement. Recommendations include strengthening inter-institutional coordination, enhancing public awareness, and ensuring the independence of oversight mechanisms to promote fair and transparent elections.